(untitled) (Nigerian Journal of Technology, 2020)
In the present study, Pelargonium sidoides (PS) extract was used in the green synthesis of AuNPs that was characterized by UV-Vis, TEM, SAED, EDS, XRD, FTIR, and DLS. UV-Vis showed a surface plasmon resonance (SPR) at ?max of 532 nm while TEM shows that the particles are predominantly spherical and monodispersed. DLS measurement indicated the particle size and the zeta potential to be 27.20 nm and -24.0 mV respectively. The in vitro stability of the hybrid particles in different solutions and buffers (pH 7 and 9) confirmed that the particles are stable over a given period. The method employed is simple, environmentally friendly, and inexpensive. Our studies suggest that the Pelargonium sidoides-gold nanoparticles (PS-AuNPs) may be safely used in biomedical applications such as drug delivery. http://dx.doi.org/10.4314/njt.v39i3.18